2015
DOI: 10.5539/gjhs.v7n2p335
|View full text |Cite
|
Sign up to set email alerts
|

Improvement Critical Care Patient Safety: Using Nursing Staff Development Strategies, At Saudi Arabia

Abstract: Intensive care units (ICUs) provide lifesaving care for the critically ill patients and are associated with significant risks. Moreover complexity of care within ICUs requires that the health care professionals exhibit a trans-disciplinary level of competency to improve patient safety. This study aimed at using staff development strategies through implementing patient safety educational program that may minimize the medical errors and improve patient outcome in hospital. The study was carried out using a quasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
2
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 23 publications
2
17
2
11
Order By: Relevance
“…Although "professional qualification" did not show differences in either the NWI-R or IWS between the technical and higher education levels in the present study, other studies have identified an association between work satisfaction, level of education and environment of practices (2,10,(14)(15) . A Brazilian study performed in several units of a university hospital, which also included the ICU, aiming to investigate work satisfaction, indicated that such satisfaction was associated with the technical level of qualification and workplace.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…Although "professional qualification" did not show differences in either the NWI-R or IWS between the technical and higher education levels in the present study, other studies have identified an association between work satisfaction, level of education and environment of practices (2,10,(14)(15) . A Brazilian study performed in several units of a university hospital, which also included the ICU, aiming to investigate work satisfaction, indicated that such satisfaction was associated with the technical level of qualification and workplace.…”
Section: Discussioncontrasting
confidence: 44%
“…The characteristics of professionals themselves, who are aged 40 years on average and have a length of work in the ICU of approximately eight years, thus being more experienced, can explain the better performance in the organization and management of ICU resources and, consequently, the better perception of the environment and greater work satisfaction (6,(13)(14) . Despite the vulnerabilities of material/technological and human resources identified by the majority of nursing professionals and low work satisfaction identified with the IWS score measure, 90.08% of these professionals reported being satisfied working in the ICU and they also assessed the environment positively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 This fact is also directly related to the quality of care and, consequently, the development of safe practices. [34][35] The satisfaction in providing patient and professional safety can be seen in the H3E11 testimony, which converges with the affirmation that the professional when adhering to the safe practices will see benefits because, once the errors are diagnosed and the failures in the processes are corrected, the employee will have better working conditions and satisfaction with the profession. 36 In addition, it means that the patient will have the benefit of receiving safe and quality assistance and the organization, in turn, will have credibility and reduction in costs.…”
mentioning
confidence: 87%
“…1,8,9 A Unidade de Terapia Intensiva (UTI) acolhe pacientes em estado crítico de saúde que necessitam de inúmeros procedimentos complexos com alto risco para infecções e EAs. 10 Alguns fatores presentes na rotina de trabalho da equipe de enfermagem em UTI podem aumentar o risco para ocorrência de EAs, como o excesso de carga horária na jornada de trabalho, stress, rotina monótona, cobrança elevada por atenção e zelo durante os procedimentos de enfermagem, poucas horas de descanso e sobrecarga de trabalho. Estas condições somadas à deficiência de conhecimento da equipe sobre o uso das metas internacionais para promoção da segurança do paciente podem interferir no aumento da vulnerabilidade do paciente aos riscos de EAs.…”
Section: Introductionunclassified